Review of the Effects of Enclosure Complexity and Design on the Behaviour and Physiology of Zoo Animals - Cristiano Schetini de Azevedo; Cynthia Fernandes Cipreste; Cristiane Schilbach Pizzutto; Robert John Young (Animals, 2023)
The complexity of the habitat refers to its physical geometry, which includes abiotic and biotic elements. Habitat complexity is important because it allows more species to coexist and, consequently, more interactions to be established among them. The complexity of the habitat links the physical structure of the enclosure to the biological interactions, which occur within its limits. Enclosure complexity should vary temporally, to be able to influence the animals in different ways, depending on the period of the day and season and throughout the year. In the present paper, we discuss how habitat complexity is important, and how it can positively influence the physical and mental states of zoo animals. We show how habitat complexity can ultimately affect educational projects. Finally, we discuss how we can add complexity to enclosures and, thus, make the lives of animals more interesting and functional.